Design of a multifunctional sample probe for transport measurements - Ozturk, Mustafa; Akdogan, Numan (Tubitak Scientific & Technological Research Council Turkey, 2018)
Herein, we describe a multifunctional sample probe equipped with a two-axis goniometer for transport measurements. The two-axis goniometer enables both computer-controlled 360 degrees out-of-plane and manual 360 degrees in-plane rotations. The multifunctional sample probe was successfully implemented to a host dewar and an electromagnet system. The developed probe is capable of performing transport measurements while fully controlling the parameters such as the magnetic and electrical fields, the angle, the temperature, and the current/voltage parameters in a wide range. The design of the multifunctional sample probe allows easy installation into different dewar and magnet systems and connection of a wide range of external devices. A software interface based on NI Labview visual programming language was developed to control the system. The setup was tested in the hysteresis loop measurements of perpendicularly magnetized Co/Pt/CoO ultrathin films with the anomalous Hall effect (AHE) method. We also performed temperature-dependent exchange bias measurements on the same ultrathin films where the developed probe revealed much better resolution compared to a standard vibrating sample magnetometry system.
Keywords: Multifunctional sample probe; magneto-transport; anomalous Hall effect; I-V characterization; perpendicular; exchange bias